Análisis y evaluación del efecto que tendría una regulación de redes multiservicios - Sanmartín Cueva, Diego (2009)
In a nation where the technological development is essential for their development, make an analysis about the consequences of the implementation of news and Enhanced technologies have a big importance. This paper seeks to analyze the different impacts that cause the implementation of multiservice networks, both in users and service providers, moreover, how the state must take control and regulate them, always seeking the benefit of society. To this has gathered all the information on the telecommunications regulatory organization in Ecuador, technologies that can be implemented and the changes needed to make for proper regulation.